Determination of Cadmium and Lead Contents in Black Tea and Tea Liquor from Iran - Ali Zazouli, Mohammad; Mohseni Bandpei, Anoshiravan; Maleki, Afshin; Saberian, Morvarid; Izanloo, Hassan (Asian Journal of Chemistry, 2010)
The aims of this research were to investigate the cadmium and lead content of several commercially available brands of tea (Camellia sinensis L) in Iran and to compare the release of cadmium and lead from them by infusion. Ten of the most widely consumed brands of Iranian and foreign black tea were purchased from local markets. Three samples of each brand were collected and analyzed. Cadmium and lead contents in the tea and tea infusions were determined by atomic absorption spectrometer after acid digestion. The results revealed that the minimum and maximum lead contents in studied tea were 0.66 ± 0.14 and 15.48 ± 0.58 μg/g for Sharzad and Sharyat tea, respectively. In addition, the minimum and maximum cadmium content was 0.09 ± 0.013 and 1.92 ± 0.38 μg/g for Ahmad and Sharyat tea, respectively. Cadmium content in Iranian tea was not significantly higher than in the foreign tea (p > 0.05), however lead was significantly higher than in the foreign tea (p < 0.05). Total cadmium contents of the dried tea Infusion that was released in the tea liquor was no detectable for all samples in the 15 min infusion, while relased 24.4 % (Sharyat tea) to 72 % (Sharzad tea) of the total lead content. The cadmium and lead contents increase in tea liquor with increasing of infusion time from 15 to 30 min. The present study suggests that tea may be a rich source of dietary heavy metal intake and metals content in tea liquor depend on infusion time. The levels of cadmium and lead determined in this study compared well with those reported for tea from some other parts of the world. Based upon the present safety standards, the tea versions selected in the present study were found to be safe for human consumption.